2009
DOI: 10.1007/s11199-008-9579-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Form of Cereal Box Characters: Different Medium, Same Disparity

Abstract: We investigated the extent to which male characters outnumber female characters on cereal boxes, and the extent to which male and female characters are portrayed in gender stereotypical ways. Cereal boxes (N= 217) from a large grocery store in the northeastern United States were examined. Characters on the front and back of the boxes were coded for gender, species (person, animal, object), age (child/adolescent, adult), and activity level (passive/sedentary, active). Male characters outnumbered female characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…S.M. Shaw (Shaw, 1994) has emphasized contemporary media upholds and reproduces present-day gender principles (Black et al, 2009;Lafky et al, 1996;McArthur, Resko, 1975) have raised concerns over how these contemporary media depictions portray culture and what impact it will have on future generations. K.A.…”
Section: Discussion Gender Stereotypes and Damaging Consequences Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…S.M. Shaw (Shaw, 1994) has emphasized contemporary media upholds and reproduces present-day gender principles (Black et al, 2009;Lafky et al, 1996;McArthur, Resko, 1975) have raised concerns over how these contemporary media depictions portray culture and what impact it will have on future generations. K.A.…”
Section: Discussion Gender Stereotypes and Damaging Consequences Of Amentioning
confidence: 99%
“…K.A. Black (Black et al, 2009) debates that due to exposure to stereotypes from a young age, youngsters adopt stereotypes and end up imitating it.…”
Section: Discussion Gender Stereotypes and Damaging Consequences Of Amentioning
confidence: 99%
“…A recent analysis of another source of images, cereal boxes, revealed that 72% of characters pictured were male while only 28% were female (Black, Marola, Littman, Chrisler, & Neace, 2009). And as before, the gender difference was more exaggerated among images of animals, of which 90% were male and 10% were female (Black et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent analysis of another source of images, cereal boxes, revealed that 72% of characters pictured were male while only 28% were female (Black, Marola, Littman, Chrisler, & Neace, 2009). And as before, the gender difference was more exaggerated among images of animals, of which 90% were male and 10% were female (Black et al, 2009). Most recently, a study of coloring books displayed patterns similar to these other forms of media with regard to animals; 82% of the animals depicted in the color books were male and 18% were female (Fitzpatrick & McPherson, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stereotyping, which we define as the creation or reinforcement of one-sided representations of persons, social groups, norms and values, is a well-known problem in some areas of marketing (de Mooij 2005), in particular Health Branding Ethics 37 sexual and gender stereotypes in advertising (Black et al 2009;Hastings et al 2010;Reid and Jones 2010;Thomas 2009). Research in social psychology suggests that being exposed to stereotype stimuli can motivate individuals to adopt behavioral assimilation, i.e., to act in accordance with the perceived character traits of the stereotype (Bargh et al 1996;Schubert and Häfner 2003).…”
Section: Stereotypingmentioning
confidence: 99%